Myocardial fibrosis in congenital heart disease - Gordon, Blanca; González-Fernández, Víctor; Dos-Subirà, Laura (Frontiers in Pediatrics, 2022)
Myocardial fibrosis resulting from the excessive deposition of collagen fibers through the myocardium is a common histopathologic finding in a wide range of cardiovascular diseases, including congenital anomalies. Interstitial fibrosis has been identified as a major cause of myocardial dysfunction since it distorts the normal architecture of the myocardium and impairs the biological function and properties of the interstitium. This review summarizes current knowledge on the mechanisms and detrimental consequences of myocardial fibrosis in heart failure and arrhythmias, discusses the usefulness of available imaging techniques and circulating biomarkers to assess this entity and reviews the current body of evidence regarding myocardial fibrosis in the different subsets of congenital heart diseases with implications in research and treatment.